Des appareils photo jetables au service d´un projet de développement : représentations paysagères et stratégies des acteurs locaux de la montagne thiernoise - Yves Michelin (Cybergeo, 1998)
In order to analyse how the representations of usual landscapes have had an influence on land use policy, an experiment has been conducted in the " montagne thiernoise, French massif central " with six elected people. Each one received one disposable camera and a list of questions about his landscape that he had to illustrate with his own pictures. An individual discussion was conducted a second time to define with each one, personal and cultural aspects of his landscapes, what he considered as beautiful or bad elements in these landscapes and what he imagined for the future.As this first test was successful, we consider that this kind of landscape analysis could be useful to prepare a development program in rural areas. Even if this method has to be better, it can soon be used by non-specialist technicians to analyse the influence of landscape representations upon local planning management decisions.